2019
DOI: 10.5644/ama2006-124.255
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Carpal Tunnel Syndrome in Patients on Chronic Hemodialysis

Abstract: <p><strong>Objectives. </strong>To determine the prevalence of carpal tunnel syndrome risk in patients on chronic hemodialysis (HD) using Levine questionnaire for assessment of carpal tunnel syndrome - related symptoms severity and patients’ functional status and to examine the relation of the determined risk with the participants’ demographic, anthropometric and laboratory data.</p><p><strong>Participants and Methods</strong>. This crosssectional study included 78 chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Hospital-based controls are likely to have other latent or undiagnosed diseases. Many studies have shown that the prevalence of CTS is significantly higher, for example, among patients with postmastectomy lymphedema or chronic hemodialysis than among the general population [ 63 , 64 , 65 , 66 ]. Using hospital patients as a control group may underestimate the true association between smoking and CTS.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital-based controls are likely to have other latent or undiagnosed diseases. Many studies have shown that the prevalence of CTS is significantly higher, for example, among patients with postmastectomy lymphedema or chronic hemodialysis than among the general population [ 63 , 64 , 65 , 66 ]. Using hospital patients as a control group may underestimate the true association between smoking and CTS.…”
Section: Discussionmentioning
confidence: 99%
“…Carpal tunnel syndrome (CTS) is the most common clinical peripheral nerve entrapment syndrome, with the highest incidence among all peripheral nerve entrapment syndromes, usually due to the hyperplasia of the transverse carpal ligament causing compression of the median nerve (1). The disease is common in those who overuse the wrist, most of which are spontaneous, and mild patients with a short course of the disease can mostly relieve symptoms after conservative treatment (2); however, it may also be secondary to fractures and fracture dislocations about the wrist, rheumatoid arthritis, diabetes, ganglion cyst, and dialysis patients (3)(4)(5)(6). In addition, tophi deposition in the flexor tendon sheath can also cause compression of the median nerve, leading to CTS.…”
Section: Introductionmentioning
confidence: 99%
“…Hemodialysis patients experiece a variety of bothersome clinical symptoms, such as carpal tunnel syndrome [ 6 , 7 ], restless leg syndrome [ 8 , 9 ], pruritus [ 8 , 10 ], poor appetite [ 8 , 11 , 12 ], anemia [ 13 ], and insomnia [ 14 ]. Some of these symptoms can be explained by the incomplete removal of middle high molecular weight uremic toxins during hemodialysis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%